2017
DOI: 10.1097/aud.0000000000000376
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Release From Masking in Children: Effects of Simulated Unilateral Hearing Loss

Abstract: Objectives The purpose of this study was twofold: 1) to determine the effect of an acute simulated unilateral hearing loss on children’s spatial release from masking in two-talker speech and speech-shaped noise, and 2) to develop a procedure to be used in future studies that will assess spatial release from masking in children who have permanent unilateral hearing loss. There were three main predictions. First, spatial release from masking was expected to be larger in two-talker speech than speech-shaped noise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 71 publications
6
27
0
Order By: Relevance
“…The smaller age effect for noise maskers than speech maskers has been interpreted as indicating that children experience little or no perceptual masking with noise maskers. This conclusion receives support from the finding that spatial segregation provides marked benefits for speech-in-speech, but only modest benefit for speech-in-noise recognition in children or adults (Corbin et al, 2017;Freyman et al, 2001). Interestingly, infants may experience perceptual masking in both noise and speech-based maskers , suggesting that the ability to perceptually isolate target speech from a noise masker may be learned.…”
Section: Introductionsupporting
confidence: 53%
“…The smaller age effect for noise maskers than speech maskers has been interpreted as indicating that children experience little or no perceptual masking with noise maskers. This conclusion receives support from the finding that spatial segregation provides marked benefits for speech-in-speech, but only modest benefit for speech-in-noise recognition in children or adults (Corbin et al, 2017;Freyman et al, 2001). Interestingly, infants may experience perceptual masking in both noise and speech-based maskers , suggesting that the ability to perceptually isolate target speech from a noise masker may be learned.…”
Section: Introductionsupporting
confidence: 53%
“…Children required a more advantageous SNR to achieve the same criterion level of performance as adults in all three masker conditions, but the magnitude of SRM was similar across age. Subsequent studies have confirmed that children benefit from target/masker differences in spatial location in the context of speech-in-speech recognition (e.g., Johnstone and Litovsky, 2006; Cameron et al, 2009; Murphy et al, 2011; Yuen and Yuan, 2014; Corbin et al, 2017). Note, however, that findings from more recent studies indicate that young children experience reduced SRM relative to older children and adults when the target stimuli and/or listening conditions are more challenging (e.g., Cameron et al, 2009; Brown et al, 2010; Yuen and Yuan, 2014; Corbin et al, 2016).…”
Section: Factors Responsible For Developmental Effectsmentioning
confidence: 92%
“…The auditory training consisted of 16 sessions where azimuth [e.g., S 0 N +90 ]). One thing to bear in mind in parts 4 and 5, was that the SRM could become negative when the noise masker was presented to the better ear (Corbin et al, 2017). It is because the participant's spatial hearing can be affected by the noise masker presented to the good ear more than the poor ear.…”
Section: Training Proceduresmentioning
confidence: 99%